Social capital and violent crimes. Analysis for 101 urban communes of Chile - Jara, Alejandro (Journal Studies of Public Policy, 2015)
This study evaluates the existence of relationship among social capital and violence, expressed in the crimes that occurred in 101 urban communes of Chile, in 2009. The hypothesis proposes that the social capital explains the different levels of violence in the city, once variables such as population density, mobility of people and critical overcrowding are controlled. We assumed that violence has a multi-causal origin. The social capital linked with others personal factors, may propitiate the violence. The results show a negative relationship among social capital and overall violent crime; and that several forms of violence can be explained by a different set of variables. The crime of robbery with violence and intimidation, where violence has instrumental character, is explained by variables associated with the opportunity to commit crimes; however, homicides are explained by structural environment variables, such as the exclusion of economic and social resources.